A low n‐6 to n‐3 polyunsaturated fatty acid ratio diet improves hyperinsulinaemia by restoring insulin clearance in obese youth. Issue 7 (18th April 2022) - Tricò, Domenico; Galderisi, Alfonso; Van Name, Michelle A.; Caprio, Sonia; Samuels, Stephanie; Li, Zhongyao; Galuppo, Brittany T.; Savoye, Mary; Mari, Andrea; Feldstein, Ariel E.; Santoro, Nicola
Abstract: Aim: To examine the determinants and metabolic impact of the reduction in fasting and postload insulin levels after a low n‐6 to n‐3 polyunsaturated fatty acid (PUFA) ratio diet in obese youth. Materials and Methods: Insulin secretion and clearance were assessed by measuring and modelling plasma insulin and C‐peptide in 17 obese youth who underwent a nine‐point, 180‐minute oral glucose tolerance test (OGTT) before and after a 12‐week, eucaloric low n‐6:n‐3 polyunsaturated fatty acid (PUFA) ratio diet. Hepatic fat content was assessed by repeated abdominal magnetic resonance imaging. Results: Insulin clearance at fasting and during the OGTT was significantly increased after the diet, while body weight, glucose levels, absolute and glucose‐dependent insulin secretion, and model‐derived variables of β‐cell function were not affected. Dietary‐induced changes in insulin clearance positively correlated with changes in whole‐body insulin sensitivity and β‐cell glucose sensitivity, but not with changes in hepatic fat. Subjects with greater increases in insulin clearance showed a worse metabolic profile at enrolment, characterized by impaired insulin clearance, β‐cell glucose sensitivity, and glucose tolerance, and benefitted the most from the diet, achieving greater improvements in glucose‐stimulated hyperinsulinaemia, insulin resistance, and β‐cell function. Conclusions: We showed that a 12‐week low n‐6:n‐3 PUFA ratio diet improves hyperinsulinaemia by increasing fasting and postload insulin clearance in obese youth, independently of weight loss, glucose concentrations, and insulin secretion.